A Prospective Audit of 805 Consecutive Patients With Penetrating Abdominal Trauma: Evolving Beyond Injury Mechanism Dictating Management. Issue 2 (February 2022) - Sander, Anthony; Spence, Richard T.; McPherson, Deidre; Edu, Sorin; Nicol, Andrew; Navsaria, Pradeep
Abstract : Background: Global trends of penetrating abdominal trauma (PAT) have seen a shift toward a selectively conservative management strategy. However, its widespread adoption for gunshot injuries has been sluggish. The purpose of this study is to compare the injury mechanisms of gunshot (GSW) and stab wounds (SW) to the abdomen in presentation, management, and outcomes. Methods: Prospective cohort study, set in Cape Town, South Africa, over 2 years. All patients presenting to the center with PAT during this time were included. Presentation, management, and outcomes were compared by injury mechanism, with a focus on the operative strategy (operative vs nonoperative). Results: During the study period, 805 patients (SW 37.6%; GSW 62.4%) with PAT were managed. Immediate laparotomies were performed in 119 (39.3%) SW and 355 (70.7%) GSW, with a therapeutic laparotomy rate of 85.7% and 91.8% for SW and GSW, respectively. Nonoperative management (NOM) was implemented in 184 SW (60.7%) and 147 GSW (29.3%) ( P < 0.001), with a 92.9% and 92.5% success rate for SW and GSW, respectively. The therapeutic laparotomy rate for the delayed laparotomies (DOM) was 69.2% for SW, and 90.9% for GSW. The accuracy of clinical assessment (with adjuncts) in determining the need for laparotomy was: GSW—92% and SW—91%. Univariate analysis revealed the mechanism not to be associated with DOM. The overall mortality rate was 7.2%, and nonfatal morbidities 22.2%. Conclusion: Although GSW is a more morbid and often fatal injury, the general principles of selective conservatism hold true for both GSW and SW, equally.